A scientometric and content analysis of research output on "Retracted Papers" indexed in Scopus - Azam Mohamadloo (Fiyz̤, 2020)
Background: This study aimed to carry out a scientometric and content analysis of articles on "Retracted Paper". Materials and Methods: The study is applied research in terms of the purpose and scientometrics descriptive in terms of type, which has been done using the content analysis. The study population is the scientific productions on "retracted paper" indexed in Scopus by early August 2019. From 2628 retrieved articles, 140 articles related to the topic were selected. The analyzed factors were publication year, country, article type, and subject. Results: The results show a significant increase in the number of articles from 2014 onwards. 159 authors from 36 countries and 160 universities/organizations participated in these articles. Reasons for retraction and the subjects of the articles were examined. The effect of retraction on the reputation of authors and the number of their scientific productions and citations were also examined. Gender and language of the corresponding author, international collaborations, the trend of retracted paper, journal impact factor, and time between publishing and retraction of papers were analyzed. Finally, the role of universities in academic Integrity education to researchers has been mentioned. Conclusion: The results indicate the need to pay more attention to academic integrity education to all stakeholders (researchers, journal editors, publishers, and reviewers) and inform them about the consequences of scientific misconduct. The education and research system, scoring system, researcher promotion system, the peer review process of journals, and the punishment system for those who commit scientific misconduct need to be revised.